AB0094 FUNCTIONAL TREG CELLS MAY BE CONVERTED INTO T EFFECTOR PHENOTYPE ON EXPOSURE TO INFLAMMATORY MILIEU IN RHEUMATOID ARTHRITIS (RA) SYNOVIAL FLUID: IN-VITRO STUDY. (2nd June 2020) - Kommoju, V.; Kavadichanda, C.; Negi, V.
Abstract : Background: The debate on functional versus numerical difference in T regulatory cell population among patients with Rheumatoid arthritis (RA) is not clear. Tregs expressing Inflammatory subset phenotype markers, such as Th1(cxcr3, Tbet) and Th17(ccr6, Rorϒ) are reported. (1) Though the reported numbers of synovial fluid tregs are higher in RA, (2) the fate of Tregs on entering the synovial inflammatory milieu from peripheral blood (PB) has not yet been investigated. Objectives: To compare Treg frequencies in PB and synovial fluid between osteoarthritis (OA) and RA To compare cytokine levels in PB and SF between OA and RA To study the effect of autologous synovial fluid on RA and OA Treg isolated form peripheral blood Methods: The Peripheral Blood (PB) and synovial fluid (SF) of RA (n=80) and OA (n=30) patients were analyzed for CD4+T-cell subset frequencies and phenotypes by flow cytometry. Cytokine concentrations in plasma and SF were measured by cytometric bead array. Tregs from 5 RA-PB and 5 OA-PB were isolated and cultured in autologous synovial fluid for 24 hrs. Phenotypic expression of Th1 and Th17 chemokines on the cell surface were analyzed by flow cytometry and expression levels of T-bet, RORγ and FOXP3 in those Treg cells were measured with quantitative real-time PCR (RT-qPCR). Results: The PB and SF frequencies of Th1, Th17 and Tregs are shown in Table 1 . The pro-inflammatory cytokines were high in the plasma and SF of RA but the anti-Inflammatory cytokines were similar (Fig 1 .A&B). Treg cells were isolated from RA and OA PB and cultured in autologous SF for 24 hrs. RA Treg showed increased cell surface expression of CXCR3+ and CCR6+ (Fig 1C ) and there was no difference in OA Treg. Gene expression studies showed an increased expression of T-bet, RORγ and decreased expression of Foxp3 in RA Tregs while there was no difference in OA Tregs before and after in-vitro culture (Fig 1D ). Conclusion: Tregs in RA may be converted to Th1 and Th17 phenotype on exposure to inflammatory cytokine in the synovial fluid, thus losing their regulatory functions. Understanding factors influencing stability of Treg cells may help improve future therapeutics. References: [1]Jinlin Miao & Ping Zhu. Functional Defects of Treg Cells: New Targets in Rheumatic Diseases, Including Ankylosing Spondylitis. Current Rheumatology Reports 2018; 20: 30 [2]Penatti et al. Differences in serum and synovial CD4+ T cells and cytokine profiles to stratify patients with inflammatory osteoarthritis and rheumatoid arthritis. Arthritis Research & Therapy.2017; 19:103 Acknowledgments: Department of Science and technology, India for the research grant. Disclosure of Interests: None declared